Inconstitucionalidad del artículo 29 de la ley orgánica de donación y trasplante de órganos, tejidos y células, en relación a la decisión de ser donantes - POVEDA RUMIGUANO, AMADO FERNANDO (2012)
The Constitution of the Republic of Ecuador is the supremacy of the Constitution says the Constitution is the supreme law and prevails over any other law, complemented, where choice shall have no legal effect. According to this provision the Constitution is on the cusp of the legal system, this is where lies the essence of rights above any other standard, by which all other rules must be issued in accordance with the Constitution, these rights are violated when the legal rules issued by the Assemblyman to regulate or ensure the rights, occur as effects deter the exercise of the rights or those that restrict or impair. The Organic Law on Donation and Transplantation of Organs, Tissues and Cells on the donation, identified in Article 29, the Ecuadorian Ecuadorians and foreigners legally resident in the country, over eighteen years, the death will become donors, unless HAVE said that in life, express, it has decided against ... This rule states that all people are donors to the time of death, except in life have expressed opposite situation. The article in this rule or otherwise, should never go against the Constitution, in this case the Act provides that all donors are obviously restricted the rights of freedom and in this context, the right to make free, the right to conscientious objection. Therefore the right thing by sticking to the rights set forth this decision should be taken by all people in life and is not an exception that had decided to donate life. I agree with organ donation, but to become donors should be pointed out a mechanism so that all people expressed in a negative or positive this will on the donation, for this does not affect the right to make free choices that we enjoy everyone also monitor and respect the right to conscientious objection. For this situation the decision to become a donor is determined unconstitutional in the Organic Law on Transplantation of Organs, Tissues and Cells, being a provision that undermine the very exercise of right, on his disability, by identifying the standard intrusive to content essential to the rights of individuals, thus being a standard vague, ambiguous and vague in his statement that determine regulations do not allow or do and not derived from the objectivity of the text. The Constitution supports this approach and said that no rule of law may restrict the content of the rights and constitutional guarantees, is complemented by all the principles and rights are inalienable, inalienable, indivisible, interdependent and of equal standing. This means that Article 29 of the Law on Organ Donation and Transplantation, Tissue and cells, is the constitutional dilemma by going against the rights to make free, and also undermines the right to conscientious objection. For this situation the presumption of donation stipulated in this law clearly restricts the right to decide freely and the right to conscientious objection.